Sequential bottom-up assembly of mechanically stabilized synthetic cells by microfluidics - Weiss, Marian; Frohnmayer, Johannes; Benk, Lucia Theresa; Haller, Barbara; Janiesch, Jan-Willi; Platzman, Ilia; Spatz, Joachim P. (Nature materials, 2018)
Compartments for the spatially and temporally controlled assembly of biological processes are essential towards cellular life. Synthetic mimics of cellular compartments based on lipid-based protocells lack the mechanical and chemical stability to allow their manipulation into a complex and fully functional synthetic cell. Here, we present a high-throughput microfluidic method to generate stable, defined sized liposomes termed ‘droplet-stabilized giant unilamellar vesicles (dsGUVs)’. The enhanced stability of dsGUVs enables the sequential loading of these compartments with biomolecules, namely purified transmembrane and cytoskeleton proteins by microfluidic pico-injection technology. This constitutes an experimental demonstration of a successful bottom-up assembly of a compartment with contents that would not self-assemble to full functionality when simply mixed together. Following assembly, the stabilizing oil phase and droplet shells are removed to release functional self-supporting protocells to an aqueous phase, enabling them to interact with physiologically relevant matrices.
Published: 16 October 2017
Gesehen am 26.11.2018